2015
DOI: 10.1007/s11920-015-0594-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Major Depressive Disorder: Top Genes and Pathways Toward Clinical Applications

Abstract: The pharmacogenetics of antidepressants has been not only a challenging but also frustrating research field since its birth in the 1990s. Indeed, great expectations followed the first evidence of familiar aggregation of antidepressant response. Despite the progress from candidate gene studies to genome-wide association studies (GWAS), results fell out the expectations and they were often inconsistent. Anyway, the cumulative evidence supports the involvement of some genes and molecular pathways in antidepressan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 168 publications
1
35
0
Order By: Relevance
“…Despite controversial pharmacogenetic findings being reported for the FKBP5 gene, results obtained in a large sample of Caucasian subjects suggested that rs1360780, rs3800373, rs4713916 and rs352428 poly-morphisms may modulate antidepressant response (Fabbri and Serretti, 2015). The effect of rs3800373 and rs1360780 on antidepressant response was confirmed in subjects of Caucasian ethnicity by a recent meta-analysis (Niitsu et al 2013).…”
Section: Genetic Polymorphismsmentioning
confidence: 96%
“…Despite controversial pharmacogenetic findings being reported for the FKBP5 gene, results obtained in a large sample of Caucasian subjects suggested that rs1360780, rs3800373, rs4713916 and rs352428 poly-morphisms may modulate antidepressant response (Fabbri and Serretti, 2015). The effect of rs3800373 and rs1360780 on antidepressant response was confirmed in subjects of Caucasian ethnicity by a recent meta-analysis (Niitsu et al 2013).…”
Section: Genetic Polymorphismsmentioning
confidence: 96%
“…SSRIs) treatment response accounts for genetic factors, progress in uncovering the particular genetic polymorphisms has been slow [112]. As described in Table 1, candidate gene studies have pointed to a number of genes and SNPs that may influence antidepressant treatment outcomes [6, 7, 8-10, 26, 27, 54], including polymorphisms within the COMT [8,30], HTR2A [54,86,121], HTR1A [26], CNR1 [26], SLC6A4 [9], NPY [6], MAOA [27,30], IL1B [7,30], GRIK4 [64], BDNF [30,86], GNB3 [30], FKBP5 [86], CYP2D6 [31,121], CYP2C19 [31,121], and ABCB1 [12,86] genes (Table 1). For example, a negative influence of a higher activity COMT 158 val/val genotype on antidepressant treatment response was shown [].…”
Section: Ssris Treatment For Major Depressive Disordermentioning
confidence: 99%
“…However, the * 17 allele associated with increased function is found in only 2.7% of East Asians and 20% of Caucasians. Poor metabolizers are likely to experience higher side effects while ultra-rapid metabolizers are likely to have worse outcomes with antidepressant treatment [23]. Genotyping for these polymorphisms is justified in clinical practice in order to optimize drug dosing for efficacy and prevention of side effects.…”
Section: Cyp450 Genes and Drug Metabolismmentioning
confidence: 99%
“…Successful antidepressant treatment response has been directly associated with a decrease in FKBP5 leukocyte mRNA expression [35]. Four SNPs within this gene have been identified as potential candidates for pharmacogenetics: rs1360780, rs3800373, rs4713916, and rs352428 [23]. Polymorphism rs352428 worsens the response to antidepressant treatment in Caucasians [36].…”
Section: Fkbp5 and The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%